Exploring the role of inflammatory parameters in predicting isthmocele formation following planned cesarean section: a study in patients with a history of one previous cesarean - Erturk, Anıl; Gokce, Gulay; Kender Erturk, Nergis (The European Research Journal, 2023)
Objectives: Isthmocele is a hypoechoic area within the lower uterine segment myometrium, resulting from a discontinuation of the myometrium at the site of a previous cesarean scar. The aim of this study was to examine the influence of maternal cellular and inflammatory status prior to Cesarean Section (CS) on isthmocele formation. Methods: This prospective observational study was conducted in a tertiary hospital and included women with a history of one previous CS. The inflammatory and cellular parameters were collected and ultrasonographic examinations were conducted in the 6th postpartum month and then analyzed. Logistic regression analysis was performed to identify potential factors influencing isthmocele formation. Results: Of the 106 patients, 31 (29.2%) were diagnosed with isthmocele after one previous CS. There were no significant differences in terms of demographical variables between the groups. However, the duration of CS was significantly longer in the isthmocele group compared to the group without isthmocele (42.58 ± 8.77 vs. 38.42 ± 9.50 minutes, p = 0.03). The neutrophil-to-lymphocyte ratio (NLR) was higher and platelet-to-lymphocyte ratio (PLR) was lower in the isthmocele group (p < 0.001). Logistic regression analysis revealed that, NLR (OR [odds ratio]: 0.23, 95% CI [confidence interval]: 0.117- 0.473, p < 0.001) and PLR (OR: 1.05, 95% CI: 1.027-1.078, p < 0.001) were identified as independent predictors for isthmocele formation after planned CS. Conclusion: Inflammatory markers, such as NLR and PLR, may contribute to the formation of isthmocele in women with a history of one previous CS, shedding light on the underlying pathophysiology.